Scabies Outbreak Investigation and Risk Factors in East Badewacho District, Southern Ethiopia: Unmatched Case Control Study - Jarso Sara; Yusuf Haji; Achamyelesh Gebretsadik (Dermatology Research and Practice)
Introduction. Scabies is one of the common public health problem but neglected parasitic diseases caused by Sarcoptes scabiei var. hominis. Global scabies prevalence in both sexes was 204 million. In Ethiopia, scabies is also a common public health issue but there is lack of studies regarding outbreak investigation and risk factors in the study area. This study was aimed to investigate the scabies suspected outbreak and risk factors in East Badewacho District, Southern Ethiopia, 2016. Methods. A community-based unmatched case control (1 : 2 ratios) study was conducted in East Badewacho District, using collected scabies line listed data and face-to-face interview to assess risk factors during October 23–30, 2016. The data were collected using structured questionnaire, and then the data were coded, entered, cleaned, and analyzed using SPSS statistical software, whereas, line listed data was entered into Microsoft excel for descriptive analyses. Odds ratios (OR) and 95% confidence interval (CI) were computed to determine associated factors. Results. A total of 4,532 scabies cases line listed with overall attack rate of 110/1,000 population. The mean age was 12 years, and most affected age group was 5–14 years. Independent risk factors found to be statistically associated with scabies infestation were age less than 15 years (AOR = 2.62, 95% CI: 1.31–5.22), family size greater than 5 members (AOR = 2.63, 95% CI: 1.10–6.27), bed sharing with scabies cases (AOR = 12.47, 95% CI: 3.05–50.94), and home being affected by flooding (AOR = 22.32, 95% CI: 8.46–58.90). Conclusion. Outbreak of scabies occurred in East Badewacho District. Age less than 15 years, family size greater than five members, sleeping with others, and home being affected by flooding are the risk factors. Providing risk factors related health education on prevention and controls especially, at community level and schools, is recommended.